Autonomic Dysfunction in Major Depressive Disorder - Jahan, Choudhury Rifat; Begum, Shelina; Ferdousi, Sultana; Uddin, Md Moyeen (Journal of Bangladesh Society of Physiologist, 2015)
Background: Cardiovascular (CV) morbidity is a major problem in patients suffering from depression as greater CV mortality is found in cardiac patients with depression. Objective: To assess cardiac autonomic nerve activity by power spectral analysis of heart rate variability in patients with Major Depressive disorder. Methods: This case control study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka during 2011. Sixty patients of both sexes with Major Depressive disorder (MDD) aged 20-50 years were enrolled. The patients were selected from the Department of Psychiatry in Bangabandhu Sheik Mujib Medical University (BSMMU). Thirty drug naive MDD patients and thirty medicated MDD patients were compared with 30 healthy control and also between them. The HRV parameters were recorded by 4 active channels, RMS Polyrite-D. For statistical analysis independent sample t-test test was used. Results: LF norm and LF/HF were significantly higher and Total power, HF power, HF norm were significantly lower in both drug naive and medicated MDD patients in comparison with those of healthy control. Conclusion: Autonomic nerve dysfunction involved both the drug naive and medicated MDD patients which was associated with higher sympathetic activity and reduced vagal modulation of the heart and sympathovagal imbalance. Antidepressent drug treatment did not have any effect on autonomic dysfunction. DOI: http://dx.doi.org/10.3329/jbsp.v9i1.22794 Bangladesh Soc Physiol. 2014, June; 9(1): 37-41